Intimate coupling of electro and biooxidation of tannery wastewater - Kanagasabi, S.; Kang, Y.L.; Manickam, M.; Ibrahim, S.; Pichiah, S. (2013)
Tannery wastewater contains high organic loadings and other pollutants, making it challenging to be treated efficiently. A combined process involving both advance oxidation process and biological treatment seems to be the best solution to achieve the regulatory standard for discharge. This investigation reports on the degradation of tannery wastewater which was represented by the removal Chemical Oxygen Demand (COD) using electrochemical process, biological degradation and finally, the combination of both processes. Electrolysis was carried out in batch reactor under different current density and dilution. Biological degradation was carried out with three isolated microbial strain and optimization of pH, nutrients, and growth factors were analyzed. The combined process involved an electrooxidation reactor connected to a column packed with immobilized biomass. Electrooxidation technique was found to obtain maximum percentage COD reduction in 73.1 at 1.5 A dm-2 using raw effluent. Bacillus Strain B proved to be superior in terms of COD reduction capabilities with a high 91.5 reduction with diluted wastewater. Biodegradation process was found to be most effective at pH 6. Intimate coupling of electro and biooxidation recorded good degradation for both raw and diluted samples, achieving 66.2 and 76.6 degradation, respectively. Â© 2013 Â© 2013 Balaban Desalination Publications.